Time and Space Between Determinism And Indeterminism - Mhalla , Kais (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
In This research we will try to show the importance of concepts that is set by philosophers and scientists of the time and space in the composition of the determinism concept or indeterminism of science and the universe as a whole, as the determinism associated with the concept of mechanical universe based on the concepts of absolute time and space, two is formed by Newton in his book "Mathematical Principles of Natural Philosophy", as well as, the determinism maintained to its influence and even it expanded its control over the new sectors of the universe in The Relative Physics at the hands of Einstein through his creativity for the hypothesis space – time continuum, and in spite of his criticism of Newton absolutes. However, the determinism will leave the scientific field to replace by statistics and probability and indeterminism in quantum physics depending on the separatist structure of time and space. Various concepts of time and space at every stage of the important stages in the history of science, then, led to a new vision and different to the principle of determinism, which led to the change of the theoretical structure of science arrived to epistemology separation between a past of science and its attendant, and this led to the adoption of a philosophical positions want to re-forme a new theory of scientific knowledge harmonious to a large extent with what has been achieved on the scientific level.